ANALISIS KEPUASAN PELANGGAN TERHADAP JASA ELANG KURIR DI TANJUNG PIAYU - situmorang, obajano; Asmarawati, Citra (LPPM Universitas Putera Batam, 2022)
Various courier services located in Tanjung Piayu are Courier Eagle. The provision of this service already has many customers every day, starting from the delivery of basic necessities, clothing, cosmetics, and household furniture. The amount of competition for courier services make the courier eagle have to provide better service to each of its customers so that customers can trust the courier eagle as a competent courier service than other courier services in tanjung piayu. The unexpected problem that is often experienced by the courier eagle as a delivery service for goods to customer is how the delivery hours of goods to customers start from 10 am to 10 pm, making customer satisfaction from courier eagles reduced.